Utility of Lugol’s iodine in assessing the margin status of early stage oral cavity cancer-could it be a simple and effective way to achieve R0 resection? - Shanmugam, Subbiah; Balakrishnan, Sathiyaseelan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: It is often challenging to distinguish between dysplastic and normal mucosa during surgery. Use of staining agents that will identify abnormal mucosa may improve results. Because Lugol’s iodine is readily available, simple to use, and cost-effective, it was chosen as the preferred staining agent. To determine the effectiveness of Lugol’s iodine application in achieving R0 resection in early-stage oral cavity malignancy and thereby leading to better outcomes after treatment. Methods: In this study we included 49 patients and randomized them into two arms. One arm we did wide excision for early-stage oral cavity cancers guided by subjective assessment of margins by surgeons and in another arm, we used Lugol’s iodine to define the margin. We analysed the margin status and thereby the need for the adjuvant therapy between these two groups. Results: In those 49 patients, two of them had microscopically positive margin. One belonged to Lugol’s iodine arm and other belonged to control arm. 17 patients had close margin at mucosal site (less than 5 mm) out of which 11 belonged to control arm and 5 belonged to Lugol’s iodine arm. Conclusions: Lugol’s iodine may be a simple and reliable method in achieving better resection margins and R0 resections for early-stage oral cavity cancer. By using this simple and cost-effective method we may reduce the possibility of ending up with positive or close margins and thereby avoiding the need of chemotherapy and radiation as adjuvant therapy in those patients.